Disrupsi Digital Terhadap Struktur Pasar Tradisional: Tantangan Bagi Pelaku Usaha Kecil - Al Awali Hidayah; Amanda Aulia Pratama; Ela Rahma Yani; Nabila Syafira; Muhammad Syahril; Fera Zora (Indo-MathEdu Intellectuals Journal, 2026)
Digital disruption has brought significant changes to traditional market structures in Indonesia, particularly through the development of digital technology, e-commerce, and online transaction systems, which have impacted consumption patterns and the level of business competition. This article aims to analyze the impact of digital disruption on changes in traditional market structures and identify the challenges faced by small businesses in navigating the digital economy era. This research uses a qualitative approach with a systematic literature review of relevant national scientific publications from the past five years. The research stages include source search, literature selection based on topic suitability criteria, and thematic analysis of key findings. The study results indicate that digitalization is driving changes in competition patterns, distribution systems, and interaction mechanisms between businesses and consumers. On the other hand, small businesses still face obstacles such as low digital literacy, limited capital, inadequate technological infrastructure, and weak innovation capacity. Nevertheless, digital disruption also opens up opportunities for market expansion and increased business efficiency if supported by adaptive policies and ongoing technological assistance. These findings emphasize the importance of synergy between the government, educational institutions, and businesses in strengthening the competitiveness of small businesses amidst the digital market transformation